Management of national security in analysis and threat assessment of Indonesian sovereignty - Novky Asmoro; Marsetio Marsetio; Susanto Zuhdi; Resmanto Widodo Putro; Rizki Putri (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
This study aims to determine the management of national security in the threat of Indonesian sovereignty. Analysis with qualitative methods is presented in the research process through several data collection methods, including in-depth interviews, literature study, observation, and focus group discussions and continued with data triangulation. Threat analysis and threat assessment approaches are carried out by applying them to several case studies both at the country level and regional security stability. There are two structural efforts that need to be made in calculating national security management, namely Threat Assessment which considers the spectrum that has a high threat risk such as natural disasters, crime, terrorists and accidents, and shifts in Threat Perception such as changes in type. from military threats to non-military threats.